IMPROVING STUDENT'S SPEAKING SKILL THROUGH DIALOGUE TECHNIQUE - rahmati ab (Journal of English Education and Social Science, 2022)
ABSTRACTThe purpose of this research is to solve students' problems in improving speaking skills, especiallyin pronunciation and grammar. Problems with students' pronunciation and grammar make theirspeech difficult to understand. Poor speaking skills can cause misunderstandings in conveyingmessages in oral communication where the researcher focuses on improving students' speakingskills in daily conversation. The subject of this study was 36 students of class X at SMAN 2Lhokseumawe. The research method used was an action research. This study conducted fivemeetings for two cycles. The first cycle was conducted in two meetings and the second cyle wasconducted in one meeting. One meeting was for pre-test and the last meeting was for post-test.The intruments used in this study were speaking tests, observation check list, an observation list,and a questionnaire The result of the study showed that the students’ responses in learningspeaking was good. They enjoyed the activities through Dialogue Technique in class by having adiscussion, sharing, and cooperating well. The students’ improvement was proved by theirspeaking test results which increased from test to test. In pretest, all of students final scores wereunder 46.67. In the cycle 1 test, no one of them got final score less than 56.67. From the cycle 2test, most of the students got final score more than 63.33. Then, the data of post-test showed thatall of the students got score more than 73.33. Based on the result above, Dialogue Technique canbe used as an alternative teaching technique to improve students’ speaking skill. I suggest theteachers to use a topic variation to make the learning process more enjoyable. Then, for the nextresearchers, they could use this study as a reference to do deeper research about teachingmethod. Finally, for the English learners, they should keep practicing speaking English every day tomake their speaking ability better.Key Words: Speaking, Dialogue